Editorial: Diversity of Southern Ocean deep-sea benthos between cosmopolitism and cryptic speciation: new species from the ANDEEP expeditions - Schüller, Myriam; Brandt, Angelika; Ebbe, Brigitte (Journal and proceedings of the Royal Society of New South Wales, 2013)
Schüller, Myriam, Brandt, Angelika, Ebbe, Brigitte (2013): Editorial: Diversity of Southern Ocean deep-sea benthos between cosmopolitism and cryptic speciation: new species from the ANDEEP expeditions. Zootaxa 3692 (1): 4-6, DOI:10.11646/zootaxa.3692.1.3